1996
DOI: 10.1139/x26-136
|View full text |Cite
|
Sign up to set email alerts
|

In-stream large woody debris loading and riparian forest seral stage associations in the southern Appalachian Mountains

Abstract: Large woody debris (LWD) is an important ecological component of mountain streams. However, the relation of LWD loading and riparian forest composition is poorly understood in the southern Appalachians. In this study, 500-m reaches of 11 riparian forest–stream systems representing a 300-year sere were inventoried and measured to obtain quantitative estimates and descriptions of in-stream LWD. Loading volumes ranged from 7.1 to 31.2 m3/100 m of stream, or between 3.6 and 13.2 kg/m2. LWD loadings were highly var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 0 publications
6
63
1
Order By: Relevance
“…Anthropogenic activities along the river basins could affect water flow rate within the wetlands and thus affect their retention abilities. The recorded water flow rates in the three wetland ecosystems were in accordance with EPA (1993) of between 0.001 to 0.603 m/s [22]. A strong positive statistically significant seasonal correlation between the recorded flow rate values for the three wetland ecosystems (Kigwal/ Figure 10 shows the mean surface water turbidity values for both dry and rainy seasons for Kigwal/Kimondi, River Nyando and River Nzoia wetland ecosystems.…”
Section: Mean Surface Water Temperature Of Selected Wetland Ecosystemssupporting
confidence: 80%
See 2 more Smart Citations
“…Anthropogenic activities along the river basins could affect water flow rate within the wetlands and thus affect their retention abilities. The recorded water flow rates in the three wetland ecosystems were in accordance with EPA (1993) of between 0.001 to 0.603 m/s [22]. A strong positive statistically significant seasonal correlation between the recorded flow rate values for the three wetland ecosystems (Kigwal/ Figure 10 shows the mean surface water turbidity values for both dry and rainy seasons for Kigwal/Kimondi, River Nyando and River Nzoia wetland ecosystems.…”
Section: Mean Surface Water Temperature Of Selected Wetland Ecosystemssupporting
confidence: 80%
“…Higher temperatures probably decrease adsorption of hydrocarbons by soil particles and the adsorbed hydrocarbons are released to water. Solubility of hydrocarbons into water is also temperature dependent, thus leading to a decrease in adsorption when temperature rises [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher volumes of woody debris were found in unlogged streams compared with logged streams in the Appalachian Mountains (Hedman et al 1996). Similarly, recent research in the Pacific Northwest observed reduced numbers of woody debris pieces in streams after logging (Bilby and Ward 1991).…”
Section: Introductionmentioning
confidence: 80%
“…Old-growth forests can contain a variety of structural features that require a long time to develop, such as large trees, snags, downed logs, and multiple canopy layers [1][2][3]. The overall stand OPEN ACCESS physiognomy has also been described as varying from containing a relatively continuous upper canopy of shade intolerant species, to a fragmented canopy, to a continuous canopy of primarily shade tolerant species [4,5].…”
Section: Introductionmentioning
confidence: 99%